2011
DOI: 10.1590/s0004-27492011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR in infectious uveitis as an alternative diagnosis

Abstract: Purpose: Uveitis is a major visual impairment disease affecting parts or the entire uveal tract and occasionally the sclera, the cornea or the optic nerve. The disease is a major cause of ocular morbidity and blindness in immunocompetent and immunocompromised patients. In this work we analyzed the sensitivity and specificity of realtime PCR to detect the etiological agent from blood, plasma, vitreous and aqueous humor and compared with the diagnostic hypothesis. Methods: Twenty-seven patients (13 male) were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 19 publications
(21 reference statements)
1
19
1
Order By: Relevance
“…Patients with uveitis of infectious and non-infectious etiologies often share similar clinical signs and symptoms at presentation, representing diagnostic challenges, especially when serology is unable to establish the diagnosis [8]. Having an early definitive laboratory-proven diagnosis is very advantageous in starting timely appropriate effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with uveitis of infectious and non-infectious etiologies often share similar clinical signs and symptoms at presentation, representing diagnostic challenges, especially when serology is unable to establish the diagnosis [8]. Having an early definitive laboratory-proven diagnosis is very advantageous in starting timely appropriate effective treatment.…”
Section: Introductionmentioning
confidence: 99%
“…On these grounds recent reports even question its utility and discourage its practice in anterior uveitis [5, 8]. Recent reports discourage aqueous PCR for the diagnosis of infectious uveitis or favour PCR of vitreous over aqueous [5, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…The use of real-time PCR as a diagnostic tool for infectious uveitis has been demonstrated by many groups (11,(19)(20)(21) . In this study, qPCR identified T. gondii infection in 37.21% of the aqueous humor samples, confirming the clinical hypothesis of toxoplasmic active focal necrotizing retinochoroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) can detect microorganism DNA and is a rapid method with high sensitivity and specificity that has been used to detect T. gondii DNA in different biological samples (8,9) . With the recent advances in molecular biology, the use of real-time PCR makes quantitative measurement of T. gondii DNA possible in patients with ocular toxoplasmosis (10)(11)(12) . Rapid recogni- tion of specific infections is important for adequate management of uveitis (13) .…”
Section: Introductionmentioning
confidence: 99%